Razões oprimidas - José Eustáquio Romão (Universidade do Minho, 2010)
Paulo Freire, along his life, asked his disciples they must not repeat him; but, instead of that, they must reinvent him in each specific context. The Oppressed Reasons' approach is a reinvention's attempt of freirian's legacy in the epistemological field. Thus, this text rescue the principle that Paulo Freire developed in Pedagogy of the oppressed - the one that proposes that only the oppressed can liberate themselves and also liberate their oppressors- applying it in the field of knowledge theory and, therefore, demonstrating the epistemological vantage of the oppressed.